2002
DOI: 10.1111/j.1744-7429.2002.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐Free Time? Damage to New Leaves of Woody Plants after Hurricane Andrew1

Abstract: All broadleaf woody plants of pinelands and hammocks (upland areas) in the northern parts of Everglades National Park were defoliated by the strong winds of Hurricane Andrew in August 1992. Most plants re‐leafed within two months of the storm, at which time we tagged newly produced leaves of eight species (five species in two hardwood hammocks and four in two pineland sites; one species was studied in both habitats), and monitored individual leaf area lost or damaged monthly for three months. We marked a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…The higher mortality induced by desiccation is explained by the fact that in WH sites the canopy was severely damaged and seedlings were more exposed to direct sunlight (Grogan et al, 2005). Our result showed an increase in herbivory and contrasts with observed in other tropical sites, where hurricanes seems to locally eliminate herbivores reducing the damage in plants (Koptur et al, 2002;Angulo-Sandoval et al, 2004;Horvitz et al, 2005).…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…The higher mortality induced by desiccation is explained by the fact that in WH sites the canopy was severely damaged and seedlings were more exposed to direct sunlight (Grogan et al, 2005). Our result showed an increase in herbivory and contrasts with observed in other tropical sites, where hurricanes seems to locally eliminate herbivores reducing the damage in plants (Koptur et al, 2002;Angulo-Sandoval et al, 2004;Horvitz et al, 2005).…”
Section: Discussioncontrasting
confidence: 82%
“…On one hand, in our study, a not yet identified lepidopteran larva (probably a moth) was found within big-leaf mahogany seeds contributing with about 60% of the total seed predation in areas hit by hurricane Dean. Other studies have documented changes in insect community after hurricanes (Koptur et al, 2002;Pascarella, 1998;Torres, 1992). For example, Torres (1992) reported lepidoptera outbreaks and the spread toward new host plants of some lepidoptera larvae.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations